TEMA BORDELES DAN SAHARA SEBAGAI SUMBER IDE PENCIPTAAN BUSANA PESTA - Wanda Kirana, Andani; Wahyuningsih, Urip (Triwikrama: Jurnal Ilmu Sosial, 2025)
The aim of the research is to find out the final results of applying Drapping to Evening Gowns. Using tulle and duces fabric as the main material. Inspired by the source of the idea taken. The process of applying Drapping begins by determining the application of Drapping on the Evening Gown. After that, the Drapping is made using the drapping technique and then stitched. The silhouette used in this clothing is silhouette I, which is a straight clothing shape from top to bottom, and is equipped with accessories. Drapping is applied on the chest, and the skirt has tassels and sequins, giving an elegant and unique impression.